2015
DOI: 10.5539/ies.v8n6p171
|View full text |Cite
|
Sign up to set email alerts
|

The Humanistic Approach to Upbringing and Education in the Creative Legacy of the Ukrainian Pedagogues of the Second Half of the 19th Century

Abstract: The article is dedicated to the study of the humanistic approach to upbringing and education in the creative legacy of the Ukrainian pedagogues of the second half of the 19 th century. Through the analysis of S. Myropolskiy's and Kh. Alchevska's pedagogical legacy, a world outlook position of scholars concerning humanisation of the educational process is shown. In the course of the research, it is found out that basis of S. Myropolskiy's and Kh. Alchevska's conception was formed by the principles, confirmed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In line with the above statement, the teacher has implemented the principles of humanistic education as explained by Anosov, et al (2015) that there are principles confirmed by humanistic pedagogy, including: (1) the principle of respect for the personality of a student or teacher as the main character of pedagogical process, (2) consideration of the characteristics of each individual, age, and individual abilities, (3) individualization of the instructional process, and (4) respect for a person's right to choose the life and career.…”
Section: Value Of Appreciation and Lovementioning
confidence: 94%
“…In line with the above statement, the teacher has implemented the principles of humanistic education as explained by Anosov, et al (2015) that there are principles confirmed by humanistic pedagogy, including: (1) the principle of respect for the personality of a student or teacher as the main character of pedagogical process, (2) consideration of the characteristics of each individual, age, and individual abilities, (3) individualization of the instructional process, and (4) respect for a person's right to choose the life and career.…”
Section: Value Of Appreciation and Lovementioning
confidence: 94%
“…The second half of the 19th century in the Russian empire, and Ukraine being its constituent part, was characterized by the considerable transformation in social, economic and political life. This period is also characterized by the development of theoretical pedagogy, the creation of pedagogical literature and journalism, various pedagogical tendencies and parties (Anosov et al, 2015). As the needs of economic development promoted widespread interest in secular education (Lutaieva, 2017).…”
Section: Introductionmentioning
confidence: 99%